Preventive oral health knowledge, attitudes and practices of patients attending selected private dental practices in Pretoria, South Africa. - Beetge, Mia-Michaela Jr (University of Pretoria, 2024)
Dissertation (MSc (Dentistry))--University of Pretoria, 2023.